Cannabinoid modulation of the dopaminergic circuitry: Implications for limbic and striatal output - Fitzgerald, Megan L. (2012)
Cannabinoid modulation of dopaminergic transmission is suggested by the ability of delta9-tetrahydrocanabinoid to affect motor and motivated behaviors in a manner similar to that produced by pharmacological manipulation of the nigrostriatal and mesocorticolimbic dopamine systems. These behavioral effects as well as analogous effects of endocannabinoids are largely mediated through the cannabinoid type 1 receptor (CB1R). This receptor is located within the substantia nigra and ventral tegmental area, which respectively house the somata of nigrostriatal and mesocorticolimbic dopaminergic neurons. The CB1R is also abundantly expressed in brain regions targeted by the efferent terminals of these dopaminergic neurons. In this review we present the accumulating anatomical and electrophysiological evidence indicating that in each of these systems cannabinoids modulate dopamine transmission largely if not exclusively through indirect mechanisms. The summarized mechanisms include presynaptic release of amino acid transmitters onto midbrain dopamine neurons and onto both cortical and striatal neurons that express dopamine D1-like or D2-like receptors functionally affiliated with the CB1 receptor. The review concludes with a consideration of the psychiatric and neurological implications of cannabinoid modulation of dopamine transmission within these networks.